Determinants of neonatal mortality in rural and urban Nigeria: Evidence from a population-based national survey - Adewuyi, E.; Zhao, Yun (Wiley-Blackwell Publishing Asia, 2016)
Background: Significant reduction in the global burden of neonatal mortality was achieved through the millennium development goals. In Nigeria, however, only a marginal reduction was realized. This study assesses the rural-urban differences in neonatal mortality rate (NMR) and the associated risk factors in Nigeria. Methods: The dataset from the 2013 Nigeria demographic and health survey (NDHS), disaggregated by rural-urban residence (n = 20 449 and 9935, respectively), was explored using univariate, bivariate, and multivariable analysis. Complex samples analysis was applied to adjust for the unequal selection probabilities due to the multi-stage cluster sampling method used in the 2013 NDHS. The adjusted relationship between the outcome and predictor variables was assessed on multi-level logistic regression analysis. Results: NMR for rural and urban populations was 36 and 28 deaths per 1000 live births, respectively. Risk factors in urban residence were lack of electricity access (adjusted OR [AOR], 1.555; 95%CI: 1.089-2.220), small birth size (as a proxy for low birthweight; AOR, 3.048; 95%CI: 2.047-4.537), and male gender (AOR, 1.666; 95%CI: 1.215-2.284). Risk factors in rural residence were small birth size (a proxy for low birthweight; AOR, 2.118; 95%CI: 1.600-2.804), and birth interval <2 years (AOR, 2.149; 95%CI: 1.760-2.624). Cesarean delivery was a risk factor both in rural (AOR, 5.038; 95%CI: 2.617-9.700) and urban Nigeria (AOR, 2.632; 95%CI: 1.543-4.489). Conclusions: Determinants of neonatal mortality were different in rural and urban Nigeria, and rural neonates had greater risk of mortality than their urban counterparts.